Using basic English grammar: form and function - Woods, Edward G.; McLeod, Nicole J. (Prentice Hall International, 1999)
This is an early grammar for elementary learners of English. The units are divided into two sections: the first explains form and structure; the second concentrates on functions performed by structures. The book contains various conversational examples of the structures covered.
OCLC: 25165104
Keywords: Anglais (langue) Grammaire Étude et enseignement; English language Grammar; English language Grammar Study and teaching